Risk of desertion profiles in students of a Colombian university - Rueda Ramírez, Sandra Milena (2020)
The objective of the study was to determine the risk profile of school desertion according to socioeconomic, institutional, academic, and individual conditions in students at different campuses of a Colombian university. A cross-sectional study was carried out with a random sample of 1897 students. The QVA-r Academic Experiences Questionnaire and the Family APGAR were administered to students. A multiple correspondence analysis was performed using the mixed classification to obtain the typologies from the coordinates of the variables in each factor. According to the profiles obtained, the one that contains the students with the highest risk of desertion includes students with a lack of adaptation and low adaptation to university life, belonging to single-parent families and reporting severe or moderate family dysfunction.